Using Parental Report to Identify Children at Risk for Poor Sleep and Daytime Problems. Issue 4 (3rd July 2020) - Gruber, Reut; Somerville, Gail; Santisteban, Jose Arturo
ABSTRACT: Objective: To examine objective sleep patterns and the daytime behavioral, emotional and academic functioning of school-age children above and below the clinical cutoff score for the Child Sleep Habits Questionnaire (CSHQ), which is a parental-report-based measure of sleep disturbances. Participants: 48 boys and 74 girls aged 7–11 years. Methods: Participants' sleep was assessed in their home environment using a miniature actigraph (AW-64 series; Mini-Mitter, Sunriver, OR, USA) for five consecutive weeknights. The parents provided their child's report card and completed a battery of questionnaires that included the CSHQ, the Child Behavior Checklist, a demographic questionnaire and a health questionnaire. Results: Children that were above the cutoff score of the CSHQ had later objectively measured sleep schedule, were less likely to obtain the recommended amount of sleep for their age, had higher levels of internalizing and externalizing symptoms and a higher prevalence of clinical levels of externalizing and internalizing problems, had lower grades in English and French as a Second Language, and were more likely to fail these subjects. Discriminant analysis revealed that information from the objective sleep and emotional/behavioral and academic measures could significantly discriminate between those with or without parent-reported sleep disturbance. Conclusion: Parental reports of sleep disturbances can be used to identify children at increased risk for sleep, emotional, behavioral and academic problems. Such questionnaires should be incorporated into clinical practice and school-based evaluations with the goal of identifying undiagnosed children who might be at risk for poor adjustment related to night- and daytime difficulties.